Co-production of chitin-glucan complex and xylitol by Komagataella pastoris using glucose and xylose mixtures as carbon source. (15th June 2017) - Araújo, Diana; Freitas, Filomena; Sevrin, Chantal; Grandfils, Christian; Reis, Maria A.M.
Highlights: Cultivation of Komagataella pastoris in glucose/xylose mixtures. Co-production of chitin-glucan complex (CGC) and xylitol was observed. Synthesis of CGC enriched in chitin with higher molecular weight. Strategy for the valorization of glucose and xylose-rich lignocellulose wastes. Abstract: Komagataella pastoris was cultivated in glucose/xylose mixtures for production of chitin-glucan complex (CGC), a cell-wall polysaccharide. The culture preferred glucose as substrate for growth, resulting in high biomass yields (0.46–0.54 g/g). After glucose depletion, xylose was consumed but no cell growth was observed, indicating K. pastoris was unable to use it for growth. Interestingly, concomitant with xylose consumption, xylitol synthesis was noticed, reaching a maximum concentration of 7.64 g/L, with a yield on xylose of 0.52 g/g. Lower CGC production was reached as the xylose content was increased in the substrate mixtures, due to the lower biomass production. Moreover, cultivation in the presence of xylitol resulted in CGC enriched in chitin with higher molecular weight. These results suggest the possibility of using K. pastoris for the co-production of CGC and xylitol using glucose/xylose-rich substrates. It may also be a strategy to tailor CGC composition and average molecular weight.